The "warrior" and "technician" types of fencers - Czajkowski, Z. (Human Movement, 2004)
The author identifies and discusses the "warrior" and "technician" types of fencers. For a typical "warrior" fencing is above all a combat sport with a strong emphasis on fighting and rivalry. Thus, the main effort and aim of the "warrior" type of fencers is to compete, fight and win at any cost. For a typical "technician" fencing is versatile, rich and complicated, based on historical heritage, sport and art. It develops motor-functional abilities, fast reaction, motor educability, motor control and co-ordination adaptability, as well as improves many personal traits, attitudes, abilities, skills, useful in life and productive work. The description, discussion and analysis of the differences between the "warrior" and "technician" types of fencers yield important problems for the fencing coach. One should not try to change the above characteristics completely (which, anyway, is almost impossible), but try to induce changes in the fencer's attitudes, taking advantage of their strong points (e.g. "warrior's" ambition and motivation; and "technician's" interest in fencing and desire to work hard). To a "warrior" the coach must explain that in order to win he must increase his knowledge and understanding of fencing; he must increase his repertoire of learned fencing actions and apply more versatile tactics in competition. To a "technician" the coach must explain that an important part of fencing is rivalry, taking part in competitions, and striving to obtain good results. The pupil should understand that he learns fencing, its history, theory, practice and methodology in order - among other aims - to win. He should then strive to use his knowledge, deep understanding of fencing and rich and versatile techniques to the best of his ability, in order to obtain better results in competitions.